The Influence Of Pesantren Education On The Development Of Students' Character - Seffiani Dwi Azmi; Arifannisa Arifannisa; Dwiyanto Dwiyanto; Ali Imron (Journal of Pedagogi, 2024)
This study aims to explore the influence of pesantren education on the development of student character in Indonesia. Islamic boarding schools are educational institutions that have an important role in shaping the character of students through a holistic approach that includes religious, moral, ethical, and social skills education. The board-based education system in pesantren allows students to live in a structured environment, where values such as discipline, responsibility, cooperation, and social solidarity are internalized through daily activities and social interaction. This study uses a qualitative method with a literature study approach to understand more deeply how pesantren plays a role in shaping the character of strong and integrity students, especially in the midst of the challenges of modernization and globalization. The results of the study show that pesantren have a significant influence in building the character of students through traditional and religious values, which remains relevant even in the face of social and technological changes. Islamic boarding schools have also begun to integrate modern skills such as entrepreneurship and digital literacy to prepare students to face global challenges. The aspects of character that are most influenced by pesantren education include discipline, social responsibility, solidarity, and independence. This research concludes that pesantren have a great contribution in forming a young generation that is moral, moral, and ready to adapt to the changing times without losing their traditional identity